Linguistic imperialism - Robert Phillipson (Oxford Univ. Press, 1997)
This book explores the contemporary phenomenon of English as an international language, and sets out to analyse how and why the language has become so dominant. It looks at the spread of English historically, at the role it plays in Third Word countries, and at the dominance of English worldwide